Meta Analysis of the Effect of School-Based Sexual Education on the Risk of Pregnancy and Human Immunodeficiency Virus Infection in Adolescents - Akmala, Jatu Kartika; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Adolescent behavior is currently worrying, many adolescents have risky sexual behavior that can lead to pregnancy and HIV. School-based sexual education is given to adolescents to provide knowledge, understanding and prevention of sexual and reproductive health, including pregnancy and HIV among adolescents. The purpose of this study was to estimate the effect of school-based sexual education on the risk of pregnancy and HIV in adolescents based on the results of previous studies.Subjects and Method: This study is a systematic and meta-analysis study. Article is analyzed by using a randomized controlled trial study design. Several databases were used, including PubMed, Science Direct, BMJ and Google Scholar. The keywords for the article search were “school-based sexual education” OR “school-based sex education” AND “human immunodeficiency virus” AND “unwanted pregnancy” OR “unintended pregnancy” AND adolescent AND “randomized controlled trial”. This study is a full-text article with a randomized-controlled trial design. Articles were collected using PRISMA Flow diagrams. Articles that met the inclusion criteria were analyzed using the Review Manager 5.3 application.Results: There were 12 articles that fulfilled the criteria for a meta-analysis with 9 studies which showed the effect of school-based sexual education on increasing pregnancy prevention behavior by 1.04 times higher compared to non-school based sexual education (RR = 1.04; 95% CI= 0.95 to 1.13; p= 0.42) and 7 studies showed the effect of school-based sexual education on increasing HIV prevention behavior by 1.02 times higher compared to non-school based sexual education (RR= 1.02; 95% CI= 0.94 to 11; p=0.60).Conclusion: School-based sexual education affected the behavior of preventing pregnancy and HIV among adolescents.Keywords: School-based sexual education, pregnancy, HIV, adolescents.Correspondence: Jatu Kartika Akmala. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: jatu.kartika@student.uns.ac.id.Journal of Health Promotion and Behavior (2021), 06(01): 67-79https://doi.org/10.26911/thejhpb.2021.06.01.07